Relationship between smartphone addiction and sleep quality among UTAR undergraduates students - Ambalakalidachayini Devi, Ravi (2020)
The smartphone addiction issue is rising over recent years. Nowadays, people are facing sleeping problems and have poor sleep quality that caused by smartphone addiction. The current study is a cross-sectional study and a survey methodology that focused to examine the relationship smartphone addiction and sleep quality among UTAR undergraduate students. A total of 176 respondents were recruited in the present study by utilizing convenience sampling, a non-probability sampling method, by distributing the online survey through Whatsapp, Facebook and QR code. The participants have been recruited which are undergraduates under the age range of 18 to 26 years old. In the present study, number of female respondents are 115 and male respondents are 61that included Chinese, Indian, Malay and other ethnicity namely Siamese and Mauritian. The result in the present study reported a significant positive correlation between smartphone addiction and sleep quality among UTAR undergraduate students through Pearson Correlation Coefficient and Independent sample t-test. However, there were no significant gender differences in smartphone addiction and sleep quality among UTAR undergraduate students. The results of the current study can be used as a source of information for further exploration of the relevant topic.